Car post-locking child detention system based on image processing / Mohd Isyraq Mohd Yussof - Mohd Yussof, Mohd Isyraq (2014)
This project presents a real Car PostLocking Child Detection System Based on Image processing which implement on field programmable logic array (FPGA) which is applied for child’s monitoring surveillance system technology, which use a camera as a sensing unit. Nowadays, there have been many reported cases of babies being left unattended in cars. Due to the carelessness, babies left in vehicles often suffocate to death. The objective of this project is to detect the presence child in a car after a car has been locked. To achieve the objective, scope of work involve will be on Digital System Design and image processing. This project uses Altera DE2-70 FPGA board as a platform. The system was designed using Quartus II software as a medium to analyze and synthesis a HDL design. Sobel edge detection technique and background subtraction was taking place in the image processing field. The result shows that two images can be compared by applying Sobel edge detection technique. The efficiency of the edge detection depended on the light intensity of the environment. High intensity lighting gives average 80% efficiency to get the optimum edge detection image. The benefit of this project is to bring awareness and prevent children from suffocating inside vehicles. After all these matters, all cars nowadays should be outfitted with some kind of safety measure or alert device to prevent a child or someone being left in a car. The benefit of this project is to bring awareness and prevent babies from suffocating inside vehicles.